LBPS 02–21 HYPERTENSION MANAGEMENT RESEARCH PRIORITIES FROM PATIENTS, CARE-GIVERS AND HEALTH CARE PROVIDERS. (September 2016) - Khan, Nadia; Flowett, Felicia; Bacon, Simon; Khan, Samia; Gerlinsky, Carling; Johnson, Lonnie; Alves, Finderson; McLean, Donna; Perlmutter, Sara; Dermer, Mark; Laupacis, Andreas; Berg, Angelique
Abstract : Objective: Patient and stakeholder oriented research is vital to improving the relevance of research. We aimed to identify the 10 most important research priorities of patients with hypertension, their caregivers and care providers (family physicians, nurses, pharmacists and dieticians) for hypertension management. Design and Method: We used the James Lind Alliance research priority setting process with a steering committee of 15 patients, care givers, care-providers and researchers. A national web based survey was launched in Canada asking patients, care givers and care providers to submit their unanswered questions on hypertension management. Respondent questions were collated and out of scope or questions answered from randomized controlled trial evidence were excluded. An interim priority setting process ranked the top 25 questions and a final priority-setting workshop of patient, care giver and care-provider stakeholders ranked the top 10 research priorities. Results: 386 respondents submitted 800 questions (200 questions excluded). Of the respondents, 78% were patients or care-givers, 29% lived in rural areas, 78% were aged 50–80 years and 75% were women. The 600 questions were distilled down to 67 unique questions ranked at the interim priority setting. The top 10 research questions included: determining the combinations of healthy lifestyle modifications to reduce the need for antihypertensive medications, stress management interventions, determining whether treatment strategies based on control of out-of-office blood pressure are superior to strategies based on conventional (office) blood pressure control; education tools and technologies to improve patient motivation and health behaviour change, management strategies for patients of Aboriginal descent or other ethnic groups, evaluating natural and alternative treatments and optimal role of different health care providers and caregivers in supporting patients with hypertension. Conclusions: These research priorities can be used to guide researchers and funding bodies on hypertension management research considered most relevant to patients, caregivers and health care professionals.